KEDUDUKAN KEKAYAAN NEGARAYANGDIPISAHKAN PADA BADAN USAHA MILIK NEGARA (BUMN) - Henny Juliany (Masalah-Masalah Hukum, 2015)
The aim of research to determine the position of state assets set aside in BUMN. The research method used is normative empirical research by using statutory approach. The research found that the First, implementation of management and accountability for the state against state assets set aside in BUMN aims to provide an important role in contributing to the state revenue for part of the profits of BUMNs will be deposited into the state budget as Non Tax Revenue (non-tax). Second, the wealth of a country that has been transformed into the capital of state enterprises, the management should be in the business paradigm (business judgment rules), but the separation of the wealth of the country has not made   the switch into a state that in spite of the wealth of the country’s wealth .